Radiographic Diagnosis of Scapholunate Diastasis in Distal Radius Fractures: Implications for Surgical Practice - Özkan, Sezai; Korteweg, Julian J.; Bloemers, Frank W.; DiGiovanni, Nicholas C.; Mudgal, Chaitanya S. (Journal of Wrist Surgery, 2018)
Background Radiographic diagnosis of scapholunate ligament injury (SLI) in the setting of distal radius fractures (DRFs) is challenging. It remains unclear to what extent radiographic diagnosis of SLI by a radiologist influences surgical decision-making regarding treatment of SLI.Purpose We aimed to (1) identify the number of times that concerns for the possibility of concurrent SLI in the setting of a DRF had been raised by the radiologists, (2) identify how often the radiologist's diagnosis was confirmed by the treating surgeon, and (3) how many of the patients with a radiographic concern for SLI by the radiologist received operative treatment for the SLI.Patients and Methods Based on Current Procedural Terminology codes, we identified 2,923 patients that were operatively treated for their DRF in 1 of 3 participating institutions in an urban city in the United States. We reviewed the medical charts of 654 patients who had a mention of scapholunate ligament (SL) distance in their radiography, surgery, or clinical notes. We then measured the SL distance and recorded patient, diagnosis, and treatment characteristics of all these patients.Results A total of 200 out of 2,923 patients (6.8%) received a radiological diagnosis of SLI. In seven of these patients (3.5%), the surgeon confirmed the diagnosis of the radiologist. Four patients (2%) had operative repair of their SLI.Conclusion Radiologists demonstrate a low threshold to identify SLI in the setting of DRFs, while the number of SLIs identified by the treating surgeon is a remarkably smaller number.Level of Evidence Level II, prognostic study.
Keywords: distal radius fractures; scapholunate diastasis; radiographic diagnosis